Echo-guided left ventricular assist device speed optimisation for exercise maximisation - Stapor, Maciej; Pilat, Adam; Gackowski, Andrzej; Misiuda, Agnieszka; Gorkiewicz-Kot, Izabela; Kaleta, Michal; Kleczynski, Pawel; Zmudka, Krzysztof; Legutko, Jacek; Kapelak, Boguslaw; Wierzbicki, Karol (Heart (British Cardiac Society), 2022)
ObjectiveCurrent generation left ventricular assist devices (LVADs) operate with a fixed rotation speed and no automated speed adjustment function. This study evaluates the concept of physiological pump speed optimisation based on aortic valve opening (AVO) imaging during a cardiopulmonary exercise test (CPET).MethodsThis prospective crossover study (NCT05063006) enrolled patients with implanted third-generation LVADs with hydrodynamic bearing. After resting speed optimisation, patients were randomised to a fixed-modified speed or modified-fixed speed CPET sequence. Fixed speed CPET maintained baseline pump settings. During the modified speed CPET, the LVAD speed was continuously altered to preserve periodic AVO.ResultsWe included 22 patients, the mean age was 58.4±7 years, 4.5% were women and 54.5% had ischaemic cardiomyopathy. Exertional AVO assessment was feasible in all subjects. Maintaining periodic AVO allowed to safely raise the pump speed from 2900 (IQR 2640–3000) to 3440 revolutions per minute (RPM) (IQR 3100–3700; p<0.001). As a result, peak oxygen consumption increased from 11.1±2.4 to 12.8±2.8 mL/kg/min (p<0.001) and maximum workload from 1.1 (IQR 0.9–1.5) to 1.2 W/kg (IQR 0.9–1.7; p=0.028). The Borg scale exertion level decreased from 15.2±1.5 to 13.5±1.2 (p=0.005).ConclusionsTransthoracic AVO imaging is possible during CPETs in patients with LVAD. Dynamic echo-guided pump speed adjustment based on the AVO improves exercise tolerance and augments peak oxygen consumption and maximum workload.